2021
DOI: 10.1002/cam4.3883
|View full text |Cite
|
Sign up to set email alerts
|

The addition of chemotherapy to adjuvant radiation is associated with inferior survival outcomes in intermediate‐risk HPV‐negative HNSCC

Abstract: Background Only high‐risk tumors with extranodal extension (ENE) and/or positive surgical margins (PSM) benefit from adjuvant therapy (AT) with concurrent chemoradiation (CRT) compared to radiation therapy (RT) in locally advanced head and neck squamous cell carcinoma (HNSCC). Optimal treatment for intermediate‐risk tumors remains controversial. We categorized patients based on their surgical pathologic risk factors and described AT treatment patterns and associated survival outcomes. Methods Patients were ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
0
6
1
Order By: Relevance
“…While the use of aST in a highly selected subgroup of patients without ENE or positive margins is allowable within the NCCN guidelines and selected patients may still benefit, our results build on existing literature suggesting aST should be rarely utilized in this setting. 21,22 Additionally, our data does not support the supposition that systemic therapies are being used by highly specialized oncologists based on a nuanced reading of the available data, since these treatments were used more frequently in community facilities and when adjuvant therapy is given at an outside facility.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…While the use of aST in a highly selected subgroup of patients without ENE or positive margins is allowable within the NCCN guidelines and selected patients may still benefit, our results build on existing literature suggesting aST should be rarely utilized in this setting. 21,22 Additionally, our data does not support the supposition that systemic therapies are being used by highly specialized oncologists based on a nuanced reading of the available data, since these treatments were used more frequently in community facilities and when adjuvant therapy is given at an outside facility.…”
Section: Discussioncontrasting
confidence: 60%
“…Our conclusion that aST in this setting is associated with inferior survival is supported by another related study using a different regional dataset. 22 All of these studies are retrospective in nature and so cannot conclude causality and do not exclude the concept that some patient or oncologic situations warrant postoperative chemoradiotherapy outside of ENE or positive margins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the retrospective analysis by Fan [ 13 ] of patients with at least three minor risk factors, the multivariate analysis indicated that a tumor invasion depth ≥ 11 mm was an independent poor prognostic factor ( p < 0.05). In contrast, Tasoulas [ 86 ], in a mixed population of HNSCC patients (42 patients with OCC, 23% of total, intermediate-risk patients), found that the addition of chemotherapy to RT increased mortality risk. In the study by Chen MM [ 81 ], a wide analysis of the NCDB for HNSCC patients subjected to PORT or POCRT—of whom 1571 (62.2%) were treated with pRT and 956 (37.8%) with pCRT, respectively, with the presence of multiple positive lymph nodes and lymph vascular invasion in about 50% of patients in both groups—did not find differences in mortality with or without lymph vascular invasion.…”
Section: Discussionmentioning
confidence: 99%
“…11 The clinical response rate was 93%, 30 of 39 (77%) patients avoided adjuvant radiotherapy, and quality of life results were favorable. 11,15 In this generally low risk population, the pathologic complete response rate was 35%. Immune checkpoint blockade (ICB) with anti-programmed cell death protein 1 (PD-1) antibodies improves survival in recurrent/ metastatic HNSCC.…”
Section: Introductionmentioning
confidence: 89%